The empirical apprehension of the normative leadership of an international organization: The example of the World Health Organization - Régis, Catherine; Foucault, Gaëlle; Larouche, Pierre; Denis, Jean-Louis; Cohen, Miriam (Lex Electronica)

(untitled) (Centre de recherche en droit public Université de Montréal, 2024)
Empirical research in law is thriving, contributing to the creation of new knowledge and providing jurists with innovative ways to study issues and phenomena. Embracing empiricism is no easy task, but the authors of this article have taken the plunge to shed light on such research. By developing two distinct methods (for two projects), they tested the empirical potential for understanding the normative leadership of the World Health Organization (WHO). Designed as a resource for those looking to explore empiricism, this article highlights both the challenges faced and the strengths of such research. The wealth of information gathered significantly enhanced the researchers’ insights into the trajectory of WHO norms and their influence on States.